Analisis Semiotika Charles Sanders Pierce dalam Novel “Berjuta Rasanya” Karya Tere Liye - Mukhammad Taufik; Suwadi Suwadi; Ilmyatur Rosidah (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This study aims to describe Charles Sanders Pierce's semiotics based on the representament/ground in the novel Berjuta Rasa by Tere Liye. This study is a qualitative descriptive study. The novel Rasa by Tere Liye as a source of research data and text excerpts in the form of narratives, dialogues, and monologues containing icons, indices, symbols as data. Data collection techniques are carried out using reading techniques and inventory techniques. The stages of data analysis techniques are carried out by means of data reduction, data presentation, explanation of research results and conclusions and verification of research results. The results of the study show that semiotics in the novel Rasa by Tere Liye are divided into: (1) icons in the form of verbal signs in the form of character conversations about other characters and nonverbal markers in the form of character activities or activities, time settings, and character reactions as many as 10 data. (2) indices in the form of verbal markers of changes in character emotions with other characters and conversations about other characters and nonverbal markers in the form of body movements/expressions, character activities or activities, character physical characteristics, settings, character thoughts or feelings, and character reactions as many as 18 data. (3) verbal marker symbols in the form of names or labels given to characters or places as many as 12 data